Prediction of lifetime cardiovascular risk and individual lifetime treatment benefit in four European risk regions: geographic recalibration of the LIFE-CVD model. (3rd October 2022) - Hageman, S H J; Lu, W; Kaptoge, S; Lall, K; Bobak, M; Pikhart, H; Kubinova, R; Pajak, A; Tamosiunas, A; Stang, A; Schmidt, B; Schramm, S; et al.
Abstract: Background: The life expectancy free of cardiovascular disease (CVD) in individuals without previous CVD can be estimated with the LIFEtime-perspective CardioVascular Disease (LIFE-CVD) model, as recommended by the 2021 ESC CVD prevention guidelines. Our aim was to systematically recalibrate the LIFE-CVD model to four European risk regions using contemporary and representative registry data. Methods and results: The LIFE-CVD model was systematically recalibrated to four distinct risk regions within Europe, using representative aggregate data on age- and sex-specific expected CVD and non-CVD mortality incidences and risk factor distributions. For external validation, 1, 451, 077 individuals without previous CVD were included from seven European cohorts, with 53, 721 CVD events and 62, 902 non-CVD deaths during follow up. After applying the recalibrated risk prediction models to external validation cohorts, C-indices (figure 1) ranged from 0.670 (95% CI 0.650–0.690) to 0.787 (95% CI 0.785–0.789). Predicted risks matched the observed risks in the CPRD data. With the recalibrated LIFE-CVD model, the estimated gain in CVD-free life expectancy from preventive therapy differed per region, for example a 50-year-old smoking women with a systolic blood pressure of 140mm Hg was estimated to gain 0.4 years of CVD-free life from 10 mm Hg SBP reduction in the low risk region, whereas this would be 1.5 years in the very high risk region (figure 2). Interpretation: By taking into account geographical differences in CVD incidence, the recalibrated LIFE-CVD model provides a more accurate tool for the prediction of lifetime risk and CVD-free life expectancy for individuals without previous CVD, facilitating shared decision-making in cardiovascular prevention options as recommended by the 2021 European Prevention Guidelines. Funding Acknowledgement: Type of funding sources: None.